Complexity of CNC Transcription Factors As Revealed by Gene Targeting of the Nrf3 Locus - Derjuga, Anna (American Society for Microbiology, 2004)
Cap'n'collar (CNC) family basic leucine zipper transcription factors play crucial roles in the regulation of mammalian gene expression and development. To determine the in vivo function of the CNC protein Nrf3 (NF-E2-related factor 3), we generated mice deficient in this transcription factor. We performed targeted disruption of two Nrf3 exons coding for CNC homology, basic DNA-binding, and leucine zipper dimerization domains. Nrf3 null mice developed normally and revealed no obvious phenotypic differences compared to wild-type animals. Nrf3(−/−) mice were fertile, and gross anatomy as well as behavior appeared normal. The mice showed normal age progression and did not show any apparent additional phenotype during their life span. We observed no differences in various blood parameters and chemistry values. We infected wild-type and Nrf3(−/−) mice with acute lymphocytic choriomeningitis virus and found no differences in these animals with respect to their number of virus-specific CD8 and CD4 T cells as well as their B-lymphocyte response. To determine whether the mild phenotype of Nrf3 null animals is due to functional redundancy, we generated mice deficient in multiple CNC factors. Contrary to our expectations, an absence of Nrf3 does not seem to cause additional lethality in compound Nrf3(−/−)/Nrf2(−/−) and Nrf3(−/−)/p45(−/−) mice. We hypothesize that the role of Nrf3 in vivo may become apparent only after appropriate challenge to the mice.